Analysis of the transgenerational iron deficiency stress memory in Arabidopsis thaliana plants - MURGIA, IRENE; Giacometti, Sonia; Balestrazzi, Alma; Paparella, Stefania; Pagliano, Cristina; Morandini, Piero A. (Frontiers in Plant Science, 2015)
We investigated the existence of the transgenerational memory of iron (Fe) deficiency stress, in Arabidopsis thaliana. Plants were grown under Fe deficiency/sufficiency, and so were their offspring. The frequency of somatic homologous recombination (SHR) events, of DNA strand breaks as well as the expression of the transcription elongation factor TFIIS-like gene increase when plants are grown under Fe deficiency. However, SHR frequency, DNA strand break events, and TFIIS-like gene expression do not increase further when plants are grown for more than one generation under the same stress, and furthermore, they decrease back to control values within two succeeding generations grown under control conditions, regardless of the Fe deficiency stress history of the mother plants. Seedlings produced from plants grown under Fe deficiency evolve more oxygen than control seedlings, when grown under Fe sufficiency: however, this trait is not associated with any change in the protein profile of the photosynthetic apparatus and is not transmitted to more than one generation. Lastly, plants grown for multiple generations under Fe deficiency produce seeds with greater longevity: however, this trait is not inherited in offspring generations unexposed to stress. These findings suggest the existence of multiple-step control of mechanisms to prevent a genuine and stable transgenerational transmission of Fe deficiency stress memory, with the tightest control on DNA integrity.